Pendidikan Islam Sebagai Benteng Moral: Kajian Konseptual Tentang Peran Pendidikan Islam dalam Pencegahan Penyakit Sosial - Ana Dhiqfaini Sultan; Syarifuddin Ondeng; Syahruddin Usman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Social pathologies, including drug abuse, juvenile delinquency, free association, and digital violence are spreading rapidly in Indonesia and posing serious threats to the moral resilience of the younger generation. This study aims to conceptually examine the role of Islamic education in preventing and addressing contemporary social pathologies, by analysing the normative foundations of the Qur'an and Hadith, causal factors from an Islamic educational perspective, and effective implementation strategies. A library research method with a descriptive-analytical approach was applied to relevant primary and secondary sources. Findings indicate that: (1) contemporary social pathologies fundamentally constitute violations of maqashid al-shari'ah; (2) root causes include weak faith, family dysfunction, social peer pressure, and limited digital-religious literacy; (3) optimally functioning Islamic education through the internalisation of tawhid, character formation, and family-school-community synergy, serves as an effective protective factor. The study concludes that Islamic education must undergo methodological transformation to address the complexity of digital-era social pathologies, while remaining grounded in the normative foundations of the Qur'an and Sunnah.